What species of Mecyna subsequalis (Herrich-Schäffer, 1854) - group occurs in highlands of Central Asia? (Lepidoptera: Crambidae, Spilomelinae) - S. Yu. Sinev; S. K. Korb (SHILAP, 2022)
By male genitalia and external characters as well as by the mtDNA COI sequence, the species from mountain of Central Asia reported earlier as Mecyna lutulentalis (Lederer, 1858) now is identified as Mecyna salangalis Amsel, 1970. The species inhabits dry steppe slopes of Hindukush, West Pamir, Central Alai and western part of Alai valley, West Tian-Shan and western part of Inner Tian-Shan. The variability of M. salangalis is shown, and the female and its genitalia are described for the first time.